2015
DOI: 10.1371/journal.pone.0127455
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing Characterization of the Microbiota from Atlantic Intertidal Marine Sponges Reveals High Microbial Diversity and the Lack of Co-Occurrence Patterns

Abstract: Sponges are ancient metazoans that host diverse and complex microbial communities. Sponge-associated microbial diversity has been studied from wide oceans across the globe, particularly in subtidal regions, but the microbial communities from intertidal sponges have remained mostly unexplored. Here we used pyrosequencing to characterize the microbial communities in 12 different co-occurring intertidal marine sponge species sampled from the Atlantic coast, revealing a total of 686 operational taxonomic units (OT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
30
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 84 publications
(103 reference statements)
7
30
2
Order By: Relevance
“…In this study, 17 bacterial phyla were identified in species H. oculata and Proteobacteria was the most dominant phylum (21.7% reads). At lower taxonomic level, the classes Alphaproteobacteria and Gammaproteobacteria were less abundant in H. oculata in our study (3.04% and 6.12%, respectively) than in Atlantic sponges (12.1% and 10.6% reads, respectively), but the class Epsilonproteobacteria was much higher in H. oculata (6.1%) than in Atlantic sponges (0.2%) [20]. According to Abe et al, (2012), Gammaproteobacteria is the dominant class in Haliclona simulant and Gelliodes carnosa whereas Alphaproteobacteria is the dominant class in some other sponges such as Halichondria panicea, Rhopaloeides odorabile, and Mycale laxissima [23].…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…In this study, 17 bacterial phyla were identified in species H. oculata and Proteobacteria was the most dominant phylum (21.7% reads). At lower taxonomic level, the classes Alphaproteobacteria and Gammaproteobacteria were less abundant in H. oculata in our study (3.04% and 6.12%, respectively) than in Atlantic sponges (12.1% and 10.6% reads, respectively), but the class Epsilonproteobacteria was much higher in H. oculata (6.1%) than in Atlantic sponges (0.2%) [20]. According to Abe et al, (2012), Gammaproteobacteria is the dominant class in Haliclona simulant and Gelliodes carnosa whereas Alphaproteobacteria is the dominant class in some other sponges such as Halichondria panicea, Rhopaloeides odorabile, and Mycale laxissima [23].…”
Section: Discussioncontrasting
confidence: 69%
“…Among 12 phyla found in Amphius huxley, the phylum Proteobacteria was the most abundant phylum (29.4% reads). Most main bacterial phyla found in A. huxleyi were also reported in other marine sponges [20][21][22].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In addition, the phyla Planctomycetes, Cyanobacteria, and Deferribacteres were common members of the H. heliophila microbiome. A recent investigation of bacterial communities in 12 intertidal sponges also reported Proteobacteria, Planctomycetes, and Cyanobacteria to be the most abundant phyla (49). While Proteobacteria is commonly the most abundant sponge-associated microbial phylum (11,12), it is worth noting that Planctomycetes and Cyanobacteria seem to be particularly abundant in intertidal sponges.…”
Section: Discussionmentioning
confidence: 98%